Implementation Of Foreign Direct Investment In Indonesia - Simaremare, Samuel Bonardo M T (Universitas Sang Bumi Ruwa Jurai, 2025)
The Importance of Foreign Direct Investment (FDI) for developing countries like Indonesia in improving living standards and promoting general welfare is crucial. Limited capital and low productivity can impact a country's income development. Indonesia is undergoing development in all aspects and requires substantial capital, including foreign funds through FDI. Although foreign investment in Indonesia has been significant, it still lags behind several Asian countries such as Malaysia, China, Singapore, Korea and Thailand. The history of foreign direct investment in Indonesia dates back to the colonial era until the New Order period. An explanation of the definition of FDI according to Law Number 25 of 2007 concerning Investment is included as a legal basis for foreign investment in Indonesia. The regulation on foreign direct investment began in 1967 with the issuance of Law Number 1 of 1967 concerning Foreign Direct Investment and Law Number 6 of 1968 concerning Domestic Investment. The Indonesian government has enacted Law Number 25 of 2007 concerning Investment as a legal umbrella to enhance the investment made by investors in Indonesia. The law aims to provide legal certainty, transparency, non-discrimination among investors, and equal treatment to both domestic and foreign investors